Semiotic analysis of Indian advertisements for mental illnesses - Mrinal, Madhur; Kumar, Upmesh; Khurana, Sarbjeet; Singh, Vijender (SPC Journal of Social Sciences, 2021)
Paper illuminates semiotic analysis of drug advertising for depression, anxiety and its influences on doctors, patients and consumers’ behavior. Analytic attention is given to visual and linguistic imagery of advertisements in USA, UK and India. This interpretation and its associated myth have been used in drug advertisements to depict effective therapeutic efficacy or effective treatment. Many of us, doctors, patients and care givers in the family should be aware of these myths of drugs claim in the print as well as in visuals of Indian advertisements for mental illnesses.